2022
DOI: 10.21037/jgo-22-61
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological prognostic factors for gallbladder carcinoma: a retrospective study

Abstract: Background: Gallbladder carcinoma (GBC) is an uncommon neoplasm with poor long-term survival. Worldwide the incidence rates vary according to geographic area. The multifactorial aetiology and the rarity of the disease limits the studies to improve outcomes in patients, since the treatment remains mostly surgical. The aim of this study was to identify clinicopathological prognostic factors for survival in patients with GBC submitted to surgery in our institution-a tertiary centre in Portugal. Also, to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Existing literature highlights signi cant survival disparities between node-negative and node-positive diseases, with 5-year survival rates ranging from 58% -77% for the former, in contrast to 0% − 45% for the latter [9]. Regional lymph node involvement is observed in 19-62% of T2 tumours and 75-85% of T3/T4 tumours, while N2 lymph node involvement is noted in 18-36% of T2 tumours and 42-71% of T3/T4 tumours [22,27]. Our study's ndings align closely with these previous reports, as the rate of lymph node positivity increased with higher pT stages: 0% in T1, 17% in T2, 54% in T3, and 100% in T4.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature highlights signi cant survival disparities between node-negative and node-positive diseases, with 5-year survival rates ranging from 58% -77% for the former, in contrast to 0% − 45% for the latter [9]. Regional lymph node involvement is observed in 19-62% of T2 tumours and 75-85% of T3/T4 tumours, while N2 lymph node involvement is noted in 18-36% of T2 tumours and 42-71% of T3/T4 tumours [22,27]. Our study's ndings align closely with these previous reports, as the rate of lymph node positivity increased with higher pT stages: 0% in T1, 17% in T2, 54% in T3, and 100% in T4.…”
Section: Discussionmentioning
confidence: 99%
“…During surgery, instruments may touch cancer cells at the margin, causing them to fall off and form an implantation metastasis[ 19 ]. Additionally, tumor dissection can sometimes increase intraperitoneal spread and growth of GC cells owing to their aggressive invasion and adhesion or growth variation.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor stage, distant metastasis, and treatment plan were independent factors affecting prognosis. Many reports have suggested a correlation between tumor stage, distant metastasis, and prognosis in patients with advanced GC[ 19 , 25 , 26 ]. This study found that CRS combined with HIPEC improves the survival time, indicating that this combination is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…GBC is the most common cancer in the biliary tract characterized by high mortality rates, late diagnosis and poor clinical presentation [ 14 , 15 ]. Despite advances in GBC therapy, the prognosis for most patients remains dismal.…”
Section: Discussionmentioning
confidence: 99%